The Application of Solar Cells for Water Filtration System - Bancha Sreewirote; Nuchtita Suttisinthong; Atthapol Ngaopitakkul (My University, 2019)
This paper explores the importance of renewable energy technologies to support global energy policy and helps to generate enough electricity to meet the demand. The system is used to convert solar energy to use with water filtration system to study the feasibility of installation in rural areas and the quality of drinking water must be standardized. Calculate the size and coordinates of the solar cell system has been proposed, including the study of the value of investment in system installation, the break-even point of investment has been introduced.
Keywords: Investment; Filtration (mathematics); Electricity system; Photovoltaic System Optimization Techniques